Impact of friction stir welding-like heat cycles on precipitates in AA7050 analysed by SAXS and numerical modelling - Henninger, Susanne; Chafle, Rupesh; Maawad, Emad; Klusemann, Benjamin; Müller, Martin; Staron, Peter (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2026)
Precipitation kinetics in AA7050 during heat cycles as they occur in friction stir welding (FSW) were studied via small-angle X-ray scattering (SAXS), X-ray diffraction (XRD) and numerical modelling using the PanPrecipitation software. Reversion experiments were conducted for the calibration of the used model and the reversion stages of dissolution, growth and coarsening of precipitates are successfully modelled. Additionally, reversion experiments on an AA7108 alloy from literature data were modelled, affirming that other AA7xxx alloys can be described with the developed model as well. The model was used to predict precipitation kinetics in AA7050-T7451 during heat cycles typically occurring in FSW, enabling the prediction of the evolution of volume fraction and precipitate size distribution of η-precipitates at elevated temperatures, matching experimental results. For instance, with increasing temperature, stronger coarsening as well as lower final volume fractions are expected. Finally, the influence of maximum temperature and welding speed on the precipitate size distribution was studied, providing guidelines for temperature-driven process design.
Keywords: Aluminum Alloy; Precipitation; Friction Stir Welding; Modelling; Pandat